The Contribution of Proton-Donor pKa on Reactivity Profiles of [FeFe]-hydrogenases - Kisgeropoulos, Effie C.; Bharadwaj, Vivek S.; Mulder, David W.; King, Paul W. (Frontiers in Microbiology, 2022)
The [FeFe]-hydrogenases are enzymes that catalyze the reversible activation of H2 coupled to the reduction-oxidation of electron carriers. Members of the different taxonomic groups of [FeFe]-hydrogenases display a wide range of preference, or bias, for H2 oxidation or H2 production reactions, despite sharing a common catalytic cofactor, or H-cluster. Identifying the properties that control reactivity remains an active area of investigation, and models have emerged that include diversity in the catalytic site coordination environments and compositions of electron transfer chains. The kinetics of proton-coupled electron transfer at the H-cluster might be expected to be a point of control of reactivity. To test this hypothesis, systematic changes were made to the conserved cysteine residue that functions in proton exchange with the H-cluster in the three model enzymes: CaI, CpII, and CrHydA1. CaI and CpII both employ electron transfer accessory clusters but differ in bias, whereas CrHydA1 lacks accessory clusters having only the H-cluster. Changing from cysteine to either serine (more basic) or aspartate (more acidic) modifies the sidechain pKa and thus the barrier for the proton exchange step. The reaction rates for H2 oxidation or H2 evolution were surveyed and measured for model [FeFe]-hydrogenases, and the results show that the initial proton-transfer step in [FeFe]-hydrogenase is tightly coupled to control of reactivity; a change from cysteine to more basic serine favored H2 oxidation in all enzymes, whereas a change to more acidic aspartate caused a shift in preference towards H2 evolution. Overall, the changes in reactivity profiles were profound, spanning 105 in ratio of the H2 oxidation-to-H2 evolution rates. The fact that the change in reactivity follows a common trend implies that the effect of changing the proton-transfer residue pKa may also be framed as an effect on the scaling relationship between H-cluster DTMA ligand pKa and Em values of the H-cluster. Experimental observations that support this relationship, and how it relates to catalytic function in [FeFe]-hydrogenases, are discussed.